Analysis of Jia ChengWen’s Experience in Treating Old Facial Paralysis with Superficial Needling of Double Needles Based on the Theory of “Strengthening Vital Qi and Eliminating Pathogenic Factors - Liang, Zhi; Zheng, Jie; Jia, Chengwen (Journal of Contemporary Medical Practice, 2025)
This article summarizes the experience of Jia Chengwen, a famous traditional Chinese medicine doctor in Shaanxi Province, in treating facial paralysis with the combination of the theory of “strengthening vital qi and eliminating pathogenic factors” and the technique of superficial needling of double needles. Professor Jia Chengwen follows the idea of “When the healthy qi exists within the body, pathogenic factors cannot invade” from the Inner Canon of Huangdi. He emphasizes “gentleness and superficiality” in his needling technique and selects acupoints “few but essential”. He believes that “deficiency of healthy qi and long-term retention of pathogenic factors” is the key to the pathogenesis of this disease, and pays attention to “strengthening vital qi and eliminating pathogenic factors” during treatment. The technique of inserting two needles at one acupoint, combined with the principle of “the meridians pass through, and the acupoints can treat the related areas”, uses gentle and superficial needling to strengthen vital qi and eliminate pathogenic factors, stimulate the meridian qi, and take “unblocking” as the application, so as to achieve quick effects when qi arrives. It has achieved remarkable effects in clinical treatment, hoping to provide reference and inspiration.